1991
DOI: 10.1080/00039896.1991.9934405
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Causes of Carbon Monoxide Intoxication: Results of an Epidemiologic Survey in a French Department

Abstract: The purpose of this study was to estimate the incidence, mortality, and causes of carbon monoxide intoxications in France. A survey was conducted in the department of the Hauts-de-Seine, which is representative of the French population. Data were collected through a headquarters that had direct contact with all department emergency organizations and to a technical laboratory. During the 3-y study, 735 cases that were related to 291 events were reported. Thirty-six patients died. The average incidence of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
1
8
0
3
Order By: Relevance
“…More than half of the incidents were attributed to this cause. This supports the findings reported by several previous studies in other countries regarding a higher number of unintentional CO poisoning incidents caused by water heaters (Cho, Chiu, Ho, & Peng, 2008;Duen˜as-Laita et al, 2001;Gajdos et al, 1991). This finding indicates that water heaters represent a serious health threat and needs further attention.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…More than half of the incidents were attributed to this cause. This supports the findings reported by several previous studies in other countries regarding a higher number of unintentional CO poisoning incidents caused by water heaters (Cho, Chiu, Ho, & Peng, 2008;Duen˜as-Laita et al, 2001;Gajdos et al, 1991). This finding indicates that water heaters represent a serious health threat and needs further attention.…”
Section: Discussionsupporting
confidence: 95%
“…It has been estimated that approximately 50,000 annual emergency department (ED) visits in the United States are due to CO poisoning (Hampson & Weaver, 2007). It seems that the mortality and morbidity due to CO exposure is similarly high in other parts of the world (Gajdos et al, 1991;Duen˜as-Laita et al, 2001;Nazari, Dianat, & Stedmon, 2010;Wilson, Saunders, & Smith, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…1998;279:685-687 EACH YEAR, unintentional carbon monoxide (CO) poisoning is estimated to cause approximately 2100 deaths in the United States 1 and is a problem in other industrialized countries as well. [2][3][4] Efforts to educate the public on how to prevent CO poisoning have focused mainly on increasing awareness of the dangers of CO and on promoting the proper maintenance of potential residential sources of CO, such as furnaces and water heaters. 2,5,6 …”
mentioning
confidence: 99%
“…Fifty seven per cent of these last unintentional deaths were related to exhaust fumes from a motor vehicle, which in most cases was stationary. A three year study of carbon monoxide poisoning in France identified 735 cases, of which 196 had domestic causes 2. The domestic sources of carbon monoxide were water heaters (57%), boilers (21%), coal stoves (9%), braziers (4%), cookers (2%), and heating devices (1.5%).…”
mentioning
confidence: 99%